Access To Informatıon And Use Of Dıgıtal Instruments In Educatıon And Student Opinions - KASIMOĞLU, Sinem (2021)
It would not be wrong to say that a transformation has started in education as in all fields since the 2000s when the Internet began to spread. In the traditional education model, the student-centered learning models take the place of the teacher understanding that stores the information in itself, directing the student to different sources and competing with each student. According to Prensky, the generation of the so-called digital natives, who was born after 1980, has its own characteristics, its propensity to technology and digital media, contrasts with the teacher from the traditional education model. It would not be wrong to say that traditional educators, whose learning processes take place in the library environment, are replaced by educators who direct the students to digital environments where millions of information can be accessed with a single click and who design their courses accordingly. From this point of view, the situation of students' use of digital tools in educational processes constitutes the problem sentence of the research. The aim of the study was to determine the awareness level of students about the use of digital tools in education, to view the digital educational tools, to determine their feelings and thoughts against the course processes carried out with interactive course applications. The questions sought in the interviews are:1) Do you use digital education elements in the course? (Do you use interactive methods when processing your lessons).2) What is the use of digital elements in your teachers' course processing and homework project preparation process?3) Do your teachers use traditional education methods or digital education practices?4) Can you evaluate the lessons you perform in interactive environments? (learning gains, contributions to you)5) Do you prefer traditional educational models and interactive teaching practices? Why is that?5) What do you understand about digital education?6) How long have you been using digital education in your education?In this study, which was conducted in order to determine the students' opinions about access to information and the use of digital tools in education, it was conducted by using ‘’qualitative research’’ method with 10 university students. As it is known, qualitative research can be defined as qualitative data collection methods such as observation, interview and document analysis, and a qualitative process in which the perceptions and events are presented in a realistic and holistic way in the natural environment. (Yıldırım, 1999) The most frequently used qualitative method is interview. Interviewing is a powerful method used to reveal people's perspectives, experiences, emotions and perceptions. (Cited by Yıldırım; A Bogdan and Biklen, 1992). Standardized Open-ended Interview: This approach consists of a series of carefully written and ordered questions, which are asked to each interviewee in the same manner and order. (Cited in Yıldırım; A Patton1987, p.112) In this study which was conducted by using interview method which is one of the qualitative research methods, standardized open ended questions were asked to the participants and their answers were recorded and analyzed. In this research, the students' level of awareness about the use of digital tools in education, their perspectives on digital education tools, their feelings and thoughts about the course processes carried out with interactive course applications were examined. According to the results of the study, it is seen that the student profile, which meets the digital world at the time of birth, e-mails, chats, uses social media, and access to research resources in new media where information is used freely, is also prone to the use of digital tools in education. It has been observed that students prefer online, online and interactive applications instead of traditional education models.